Google Workspace Based Management Model in Improving the Effectiveness of Guidance and Counseling Services - Anugraheni, Dina Widianti; Dwikurnaningsih, Yari; Satyawati, Sophia Tri (Universitas Pendidikan Ganesha, 2023)
The management of the guidance and counseling program is an integral part of education services in schools which will influence the success of counseling services. The implementation of guidance and counseling management in schools has yet to be carried out as it should be because of the obstacles that guidance and counseling teachers face. This research aims to develop a guidance and counseling management model based on Google Workspace. This type of research is research and development (Research and Development) using the Borg and Gall model. The research subjects consisted of two media experts, two material experts, and six guidance and counseling teachers as practitioners. Data collection techniques were carried out using closed and open questionnaire instruments. Data analysis techniques use mixed methods (Mixed Methods) with a mixed combination model (Concurrent Mixed Methods). Qualitative data were analyzed using the Miles and Huberman model quantitative data were analyzed using quantitative descriptive techniques with mean and percentage. The results of the validity analysis and product trials are very good. Based on the results of this analysis, the guidance and counseling management model based on Google Workspace is feasible and effective for use in carrying out guidance and counseling management in schools. They were expected that counseling teachers could consistently take advantage of following the steps that have been made so that the effectiveness of the guidance and counseling services provided can be further increased.